Regression Test Reduction for Object-Oriented Software: A Control Call Graph Based Technique and Associated Tool. (11th April 2013) - Frechette, Nicolas; Badri, Linda; Badri, Mourad
Abstract : This paper presents a selective regression testing technique and an associated tool for object-oriented software. The technique is based on the concept of Control Call Graphs, which are a reduced form of traditional Control Flow Graphs . It uses static analysis of the source code of the program. The developed tool (1) identifies the Control Call Paths potentially impacted by changes, (2) selects, from an existing test suite, the appropriate test cases, and (3) generates new JUnit test cases for control call paths that are not covered by existing tests (new ones, or those whose structure has been modified after changes). In this way, the approach supports an incremental update of the test suite. The selected JUnit test cases, including the new ones, are automatically executed. Three concrete case studies are reported to provide evidence of the feasibility of the approach and its benefits in terms of reduction of regression testing effort.